2022
DOI: 10.3390/ijerph19148682
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Work Schedule of Nurses Related to the COVID-19 Pandemic and Its Relationship with Sleep and Turnover Intention

Abstract: Background: This study aimed to investigate whether different types of changes in the work schedule of nurses working rotating shifts during the COVID-19 pandemic were associated with sleep duration, sleep quality, and turnover intention. Methods: Cross-sectional questionnaire data from 694 nurses participating in the SUrvey of Shift work, Sleep and Health (SUSSH) were collected between the first and the second wave of the COVID-19 pandemic in Norway. A total of 89.9% were female, and mean age was 44.6 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The schedule and work hour characteristics for the year 2021, as compared to those for 2019, showed that nurses worked more long shifts in the former. This finding was consistent with Djupedal [32] and Tabrizi et al [33], who found that approximately 17% of nurses reported experiencing changes in their work schedules due to the COVID-19 pandemic, mostly in an increased number of long workdays. It is known that long work hours increase fatigue, the risk for reduced performance on the job, obesity, injuries, and a wide range of chronic diseases [34][35][36].…”
Section: Resultssupporting
confidence: 87%
“…The schedule and work hour characteristics for the year 2021, as compared to those for 2019, showed that nurses worked more long shifts in the former. This finding was consistent with Djupedal [32] and Tabrizi et al [33], who found that approximately 17% of nurses reported experiencing changes in their work schedules due to the COVID-19 pandemic, mostly in an increased number of long workdays. It is known that long work hours increase fatigue, the risk for reduced performance on the job, obesity, injuries, and a wide range of chronic diseases [34][35][36].…”
Section: Resultssupporting
confidence: 87%
“…Several studies have demonstrated that overtime negatively affects the health and well-being of caregivers’ quality of care. 22 , 23 Before the pandemic, Ball et al survey of nurses reported that shifts of more than 12 hours were associated with poor quality of care ratings, higher rates of care left undone, and the longer the shift, the higher the dissatisfaction level. 24 Jarrar et al examined the associations between nursing duty hour length on nurses’ reported quality and safety in Malaysian hospitals.…”
Section: Introductionmentioning
confidence: 99%
“… 26 , 27 During the pandemic, frequent changes in nurses’ schedules and the extension of the world emergency to combat COVID‐19 were associated with increased intent to leave and resign from their jobs. 22 A recent study demonstrated that nurses who provided treatment for COVID‐19 patients had higher intent to leave their jobs. 28 …”
Section: Introductionmentioning
confidence: 99%
“…Nurse turnover significantly contributes to nurse shortages (Xu et al., 2021). During the COVID‐19 pandemic, changes in work environments for nurses affected their psychological and physical health and well‐being, which led to increased turnover intention (Djupedal et al., 2022; Labrague & de Los Santos, 2021). Nurse turnover adversely affects nurse and patient outcomes, which can harm the quality of care and patient safety (Bae, 2022).…”
Section: Introductionmentioning
confidence: 99%